Acoustic model of the human outer ear - Melloui, J.; Bouattane, O.; Bakkoury, J. (International Journal of Engineering and Technology, 2018)
The outer ear is an important part of the human auditory periphery. Its main function is to amplify the incoming sound signal. This amplifi-cation depends on the length and the shape of the ear canal and the concha.There are various techniques used to model the outer ear, including physical models, finite element models, and electroacoustic models. Current electroacoustic models assume a uniform or gradually varying cross-section in a discontinuous manner of the ear canal.In this paper, an acoustic model is developed and considers four types of acoustic resonators to take account for the variability of cross sec-tion along the outer ear. Our model is validated against results encountered in the literature. The validated model is used in a parametric study to analyze the effect of the concha and the residual ear modelling on the frequency response of the outer ear